INTELLIGENCE DECISION-MAKING IN INTERNATIONAL LAW: THE VALUE OF EVIDENCE AND LEGAL RESPONSIBILITY IN CRIMINAL PROCEDURE LAW THE INFLUENCE OF THE PRINCIPLE OF PARTY AUTONOMY ON THE COURT’S ADAPTATION TO INTERNATIONAL TREATIES" - YU CUI LAN (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: International treaties play an important role in unifying the rules of foreign-related civil and commercial affairs.Many international treaties clearly recognize the principle of party autonomy, such as giving parties a wide range of choices in terms of the application of contract law and the effectiveness of arbitration agreements. At the same time, international treaties have also established mandatory clauses to impose necessary restrictions on the autonomy of the parties in order to safeguard the purpose of the treaty and the international public interest.For example, in the fields of consumer protection, labor contracts, etc., international treaties often restrict the parties’ free choice of the scope of applicable law.